THE ANALYSIS OF SEMI INTENSIVE NATIVE CHICKEN FARMING IN RURAL COMMUNITIES - Wantasen, E.; Elly, F.H.; Santa, N.M. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The study was aimed to determine the income for semi intensive native chicken farming and todetermine the factors influence it. The study was conducted by survey method and direct interview usingquestionnaire to 35 members of farmers group “Poyuyanan” in Poyowa Besar Village, SouthKotamobagu Dstrict North Sulawesi Province. Data were analyzed by using descriptive and quantitativeanalysis using multiple regression analysis of Cobb-Douglass model. The result showed that farmer withan average ownership of 8 hens could obtain income equivalent to 37.9 kg of rice per month. Theregression analysis showed that altogether the dependent variables had effect to income as much 81.2%(R2 = 0.821). Partially variables that could increase farmers’ income were hatching rate, number ofproductive hen, cost of production and number of eggs hatched. Mortality was the only variable thatdecreased farmers’ income. Cost of production in semi intensive native chicken farming which mainlyfor buying feed could increase the production and income for farmers that in turn would support foodavailability of rural communities in Poyowa Besar Villages